Study on hourly temperature features over Mumbai, Thiruvananthapuram and Minicoy during 1969-2012 (MAUSAM, 2016)
Amongst all the climatic elements, temperature plays a major role in detecting and analyzing climatic change and its impact. The variability in resident time of the surface temperature is studied to investigate whether any change in temperature has taken place. Analysis of the results is presented for Mumbai, a mega city with large change in land-use pattern, Thiruvananthapuram, a semi-urban city with moderate changes in land-use pattern and Minicoy, an Island city without much change in land-use pattern. These three places representing varying geographical locations and climatic conditions are unique in nature, however having uniform maritime influence. It is revealed that the change is large in Mumbai in comparison with others as expected. The study proposes a new methodology based on the resident time of temperatures and its trend and could be used as a tool for relative ranking of cities and to gauge the source and sink regions of climate change forcing. The resident time of temperatures shows increasing trend above the mean temperature and decreasing trend below the mean temperature of the initial decade. Decadal linear increasing trends in mean temperatures are 0.256 °C, 0.159 °C and 0.146 °C per decade for Mumbai, Thiruvananthapuram and Minicoy respectively. This confirms the effect of global warming unequivocally irrespective of urban effect. Decadal linear increasing trends in mean temperature during non-monsoon season for Mumbai, Thiruvananthapuram and Minicoy are 0.315 °C, 0.155 °C and 0.181 °C per decade respectively. The rate of increase of mean temperature for Mumbai and Minicoy during monsoon season is 0.143 °C and 0.081 °C per decade respectively, are significantly less than the decadal trend in annual mean, which suggests that rainfall activity seems to be the correction factor for the increasing trend in the annual mean temperature which otherwise would have been a higher value. However, the rate of increase of mean temperature for Thiruvananthapuram during monsoon season for the study period is 0.172 °C per decade, which is slightly higher than the decadal trend in annual mean. Noticeable changes in resident time during monsoon season are in conformity with change in rainfall patterns.